Examining the Ruling on Insulting a Believer from the Perspectives of Shia and Sunni Jurists - Fateme Ansari (پژوهش‌های فقهی مسائل مستحدثه)
One of the fundamental principles for every individual in society is the integrity of their personal and social identity, along with their dignity and honor, which is emphasized in Islam. Therefore, any form of insult, humiliation, or abusive language directed at a person's dignity and honor is strictly prohibited. Insulting a believer refers to the act of cursing and using derogatory language, which is discussed in various fiqhi contexts, such as Hudud (limits) and Makasib Muharamah (unlawful earnings). The issue of insults is a primary concern worldwide, encompassing extensive political, social, ethical, psychological, and propagandistic dimensions. Given the significance of this topic, this study explores the concept of insults while examining the ruling on insulting a believer from the perspectives of both Shia and Sunni jurists. The findings indicate that insulting a believer is deemed unlawful in Islamic law according to all Islamic sects. This research employs a descriptive-analytical methodology.